“Anjos da caridade”: experiências femininas no processo de abolição da escravidão em Porto Alegre (RS/ Séc. XIX-XX) - Dihl, Tuane Ludwig (Universidade do Vale do Rio dos Sinos, 2021)
This thesis proposes to analyze several female experiences in the process of abolition of slavery in Porto Alegre, bringing visibility to its agents and consequent actions in public political spaces in the city. A wide and varied group of civil, religious, notarial, and printed sources were used to accomplish this goal, which was glimpsed from theoreticalmethodological references from micro-history, like prosopography and biography, and from the combination and interchange of qualitative and quantitative approaches. From the obtained results, it was found a relevant number of young and ladies, socially white and from the wealthiest society segments, occasion their trajectories in different abolitionism perspectives - from the organized group to the daily level. As members of abolitionist societies, promoting actions within and through them, or as ladies directly dealing around the freedom of their slaved people, these women tested the gender limits imposed on them. Wisely and inventively mobilizing their resources, it was possible to note a relevant amount of abolitionists creating and maintaining their own operation spaces in segments a priori understood as male restricted spaces.
Keywords: Mulheres; Abolicionismo; Gênero; Agências femininas; Porto Alegre; Women; Abolitionism; Gender; Women’s agencies; ACCNPQ::Ciências Humanas::História